COVID‐19 and psoriasis: Should we fear for patients treated with biologics?. Issue 4 (5th May 2020) - Amerio, Paolo; Prignano, Francesca; Giuliani, Federica; Gualdi, Giulio
Abstract: The new coronavirus pandemic poses question and challenges for dermatologists. One of question is if psoriasis patients treated with immunomodulating and immunosuppressive drugs have to discontinue their treatment in the midst of fears for the infection and its consequences. One of the challenges is how can we support our patients in this critical time. Previous coronaviruses outbreaks reports, current published evidences on pathogenesis and on clinical reports of COVID infection in immunosuppressed patients are used to make a scientifically based decision.